WNT1-inducible signaling pathway protein 1 regulates kidney inflammation through the NF-κB pathway. Issue 1 (14th January 2022) - Wang, Bo; Ding, Chenguang; Ding, Xiaoming; Tesch, Greg; Zheng, Jin; Tian, PuYun; Li, Yang; Ricardo, Sharon; Shen, Hsin-Hui; Xue, Wujun
Abstract: Inflammation is a pathological feature of kidney injury and its progression correlates with the development of kidney fibrosis which can lead to kidney function impairment. This project investigated the regulatory function of WNT1-inducible signaling pathway protein 1 (WISP1) in kidney inflammation. Administration of recombinant WISP1 protein to healthy mice induced kidney inflammation (macrophage accrual and production of tumor necrosis factor α (TNF-α), CCL2 and IL-6), which could be prevented by inhibition of nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB). Furthermore, inhibition of WISP1, by gene knockdown or neutralising antibody, could inhibit cultured macrophages producing inflammatory cytokines following stimulation with lipopolysaccharides (LPSs) and kidney fibroblasts proliferating in response to TNFα, which both involved NF-κB signaling. Kidney expression of WISP1 was found to be increased in mouse models of progressive kidney inflammation-unilateral ureter obstruction (UUO) and streptozotocin (STZ)-induced diabetic nephropathy (DN). Treatment of UUO mice with WISP1 antibody reduced the kidney inflammation in these mice. Therefore, pharmacological blockade of WISP1 exhibits potential as a novel therapy for inhibiting inflammation in kidney disease.